Neha Choudhary - Choudhary, Neha; Prakash, S. Bhanu; Kumar, Sandeep (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Pulse Width Modulation variable speed drives are used in so many industrial applications in which higher performance is required. Low power loss, ease of implementation and control, no temperature variation are few advantages of PWM based switching. Improvements in power electronics system is due to the development of power electronics and semiconductor technology. A 3-phase voltage source inverter provides variable voltage and frequency which is supplied to ac drives. In ac motor drives, it is possible to control both magnitude and frequency of current and voltage which are applied to the motor is only due to SPWM inverters. Hence PWM inverters fed motor drives are more variable and offer a wide range of better efficiency and provides higher performance when compared to fixed frequency drives. Here open loop simulation and analysis of PWM inverter fed induction motor is carried out.